A sponge-templated sandwich-like cobalt-embedded nitrogen-doped carbon polyhedron/graphene composite as a highly efficient catalyst for Zn–air batteries. Issue 2 (16th December 2019) - Cai, Jia-Jun; Zhou, Qing-Yan; Liu, Bing; Gong, Xiao-Fei; Zhang, Yun-Long; Goh, Kokswee; Gu, Da-Ming; Zhao, Lei; Sui, Xu-Lei; Wang, Zhen-Bo
Abstract : Sandwich-like Co-embedded N-doped carbon polyhedron/graphene with a hierarchical porous structure was fabricated through a solution dip-coating method using sponge templates. Abstract : Non-noble metal materials are regarded as the most promising catalysts for the oxygen reduction reaction (ORR) to overcome the inherent defects of Pt-based catalysts, like high cost, limited availability and insufficient stability. Here, we fabricate sandwich-like Co encapsulated nitrogen doped carbon polyhedron/graphene (s-Co@NCP/rGO) via a facile and scalable strategy by loading Co-based zeolitic imidazolate framework (ZIF-67) and graphene oxide (GO) layers individually on a polyurethane (PU) sponge template. The 3D sandwich structure is maintained with the assistance of the sponge template, which promotes the uniform dispersion of ZIF-67-derived Co embedded nitrogen doped carbon polyhedra (Co@NCP) and prevents the graphene plates from agglomerating during the annealing process. The final product demonstrates considerable catalytic performance for the ORR with a half-wave potential of 0.85 V, preferable stability and increased poisoning tolerance by comparison to 20 wt% Pt/C, which stems from the 3D sandwich-like structure, N/Co-doping effect, large accessible surface area and hierarchical porous structures. The excellent ORR performance of the catalysts means that they can be utilised in a Zn–air battery as cathode catalysts. During such a demonstration, s-Co@NCP/rGO shows a high open-circuit voltage of 1.466 V, remarkable long-term durability and an outstanding peak power density of 186 mV cm −2, which shows its high potential as a prospective alternative for widespread practical application in the field of non-noble metal ORR catalysts.